Assessing Efficiency Performance in the Serbian Insurance Industry with DEA Model (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The insurance industry develops financial institutions and reduce uncertainties by improving financial resources. The main goal of this paper is to assess the efficiency performance of Serbian insurance companies and to check the influence of the important profitability drivers on the efficiency scores in terms of the whole insurance market. As the market develops For the rapidly developing market authors decide to find a tool for assessing efficiency performance in the insurance industry. In some paper we found that the authors measure efficiency of insurance companies, but we decided to use two-phase analysis, DEA in the first, and a Tobit regression in the second phase.